Under-utilization of antenatal care services in Timor-Leste: Results from Demographic and Health Survey 2009-2010 - Khanal, V.; da Cruz, J.; Mishra, S.; Karkee, R.; Lee, Andy (BioMed Central Ltd., 2015)
Background: Timor-Leste is a young country in the Asia-Pacific region with a high maternal mortality rate of 557 per 100,000 live births. As most maternal deaths can be prevented by providing quality antenatal care (ANC) and skilled assistance during childbirth, understanding the barriers to the utilization of ANC services can enhance program implementation. This study aimed to investigate the prevalence and factors associated with the under-utilization of ANC services in Timor-Leste. Methods: Timor-Leste Demographic and Health Survey (TDHS) 2009-2010 was a nationally representative multi-stage cross-sectional study involving 11,463 households and 9,828 childbirths. Information on last born child was recorded for 5,895 mother-child pairs. Factors influencing under-utilization of ANC were assessed using hierarchical logistic regression analysis. Results: Only 3311 (55.2, 95 % confidence interval (CI) 53.1 to 57.3 %) made the recommended four ANC visits, while 2584 (44.8; 95 % CI 42.7 to 46.9 %) of them reported attending three or less ANC services. Significant factors positively associated with the under-utilization of ANC were low wealth status (odds ratio (OR) 2.09; 95 % CI 1.68 to 2.60), no maternal education (OR 1.54; 95 % CI 1.30 to 1.82) or primary maternal education (OR 1.21; 95 % CI 1.04 to 1.41), no paternal education (OR 1.34; 95 % CI 1.13 to 1.60), and having a big problem in permission to visit health facility (OR 1.65; 95 % CI 1.39 to 1.96). Conclusions: Despite the apparently good progress made in re-establishing the healthcare infrastructure, 45 % of mothers remained in need of a focused intervention to increase their use of ANC services. Further prenatal care program should pay attention to women with low wealth status and those and their partners who are uneducated. Moreover, women should be encouraged to make decision on their own health.